The temperature of growth and sporulation modulates the efficiency of spore-display in Bacillus subtilis - Petrillo, Claudia (Microb Cell Fact, 2020)
BACKGROUND: Bacterial spores displaying heterologous antigens or enzymes have long been proposed as mucosal vaccines, functionalized probiotics or biocatalysts. Two main strategies have been developed to display heterologous molecules on the surface of Bacillus subtilis spores: (i) a recombinant approach, based on the construction of a gene fusion between a gene coding for a coat protein (carrier) and DNA coding for the protein to be displayed, and (ii) a non-recombinant approach, based on the spontaneous and stable adsorption of heterologous molecules on the spore surface. Both systems have advantages and drawbacks and the selection of one or the other depends on the protein to be displayed and on the final use of the activated spore. It has been recently shown that B. subtilis builds structurally and functionally different spores when grown at different temperatures; based on this finding B. subtilis spores prepared at 25, 37 or 42 °C were compared for their efficiency in displaying various model proteins by either the recombinant or the non-recombinant approach. RESULTS: Immune- and fluorescence-based assays were used to analyze the display of several model proteins on spores prepared at 25, 37 or 42 °C. Recombinant spores displayed different amounts of the same fusion protein in response to the temperature of spore production. In spores simultaneously displaying two fusion proteins, each of them was differentially displayed at the various temperatures. The display by the non-recombinant approach was only modestly affected by the temperature of spore production, with spores prepared at 37 or 42 °C slightly more efficient than 25 °C spores in adsorbing at least some of the model proteins tested. CONCLUSION: Our results indicate that the temperature of spore production allows control of the display of heterologous proteins on spores and, therefore, that the spore-display strategy can be optimized for the specific final use of the activated spores by selecting the display approach, the carrier protein and the temperature of spore production.